ChemInform Abstract: Convenient Access to Strained Trisubstituted 2‐Azetines from Enals and Chloramine‐T in Aqueous Media. Issue 15 (25th March 2013) - Singh, Atul K.; Chawla, Ruchi; Yadav, Lal Dhar S.
Abstract Key features of this reaction are easily accessible substrates, operational simplicity, wide substrate scope and ambient temperature.